ANALISIS PENERAPAN PSAK 409 TENTANG AKUNTANSI ZAKAT, INFAK, DAN SEDEKAH DALAM MENINGKATKAN TRANSPARANSI DAN AKUNTABILITAS LAPORAN KEUANGAN PADA BAZNAS SUMATERA UTARA - Zahra Amalia Khairani; Yenni Samri Juliati Nasution; Wahyu Syarvina (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
This study aims to analyze the implementation of PSAK 409 concerning Accounting for Zakat, Infaq, and Alms in enhancing the transparency and accountability of financial statements at BAZNAS North Sumatra Province. The research method employed is descriptive qualitative, with data collection conducted through in-depth interviews and documentation studies. The results indicate that BAZNAS North Sumatra has met the elements of technical accountability through cash-based fund recognition, strict fund separation, and the use of the SIMBA application for integrated reporting. Transparency is realized through the open publication of audited financial statements on the institution's official website to build public trust. However, such accountability and transparency are still hindered by dependence on the centralized system, limited human resource competence regarding the latest standards, and information asymmetry on the mustahik side concerning aid details. This study suggests increasing human resource capacity and optimizing public communication so that accountability is not merely an audit formality but becomes an inclusive organizational culture for all stakeholders